Klasifikasi Bahan Berbahaya dan Beracun di Bengkel Non Metal dengan Menggunakan Hazmat Tool - Novitrie, Nora Amelia; Muhammad Anis Senoaji; Agung Nugroho (Journal of Research and Technology, 2022)
Non-metal workshops is a placed used in the manufacture of wooden ships from the beginning to the final stages such as painting ships and sanding. Non-metal workshops use chemicals that are included in the Hazardous and Toxic Materials (B3) class. Safe storage of B3 is not available because no previous classification was carried out. Therefore, it is necessary to classify it using the Hazmatt Tool and design for safe storage. The conclusion obtained is that B3 in non-metal workshops is compatible, meaning that it can be stored in one cupboard and one room. B3 in non-metal workshops includes hazard class 5.2 organic peroxide, class 3 flammable liquid, class 4.1 flammable solid and recommended storage cabinets. B3 uses stainless steel material with a finishing coating of epoxy resin, acid & chemical resistant (resisting acid, heat, water) and if stored in a drum, you must use a pallet with a length of 135 cm and a width of 135 cm, so 1 pallet can accommodate 6 drums of polyester resin.